Analisis Bibliometrik Publikasi Isu Kebocoran Data Menggunakan VOSviewer - Hanissa Rizki Kurnia; Aisyah Zahrah; Elvia Ichsazene Dina Adha; Nur Aini Rakhmawati (UIN Sunan Kalijaga Yogyakarta, 2023)
Data leakage can harm individuals who experience it, such as identity theft, financial fraud, or even physical security threats. This study aims to analyze scientific publications and research activities in data leakage using bibliometric techniques by involving quantitative analysis using a set of journals as reference sources. The literature for this study was obtained using Publish or Perish software with the keyword